2016
DOI: 10.1038/srep32366
|View full text |Cite
|
Sign up to set email alerts
|

Aiptasia sp. larvae as a model to reveal mechanisms of symbiont selection in cnidarians

Abstract: Symbiosis, defined as the persistent association between two distinct species, is an evolutionary and ecologically critical phenomenon facilitating survival of both partners in diverse habitats. The biodiversity of coral reef ecosystems depends on a functional symbiosis with photosynthetic dinoflagellates of the highly diverse genus Symbiodinium, which reside in coral host cells and continuously support their nutrition. The mechanisms underlying symbiont selection to establish a stable endosymbiosis in non-sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(139 citation statements)
references
References 66 publications
6
130
3
Order By: Relevance
“…In the case of cnidarians, while broad knowledge on their association with Symbiodinium is available, there are still relatively few studies on the larva-Symbiodinium association (Rodriguez-Lanetty et al, 2006;Voolstra et al, 2009b;Schnitzler and Weis, 2010;Wolfowicz et al, 2016). Approximately 80-90% of reef-building coral species (Scleractinia) are broadcast spawners and acquire symbionts horizontally (Harrison and Wallace, 1990;Baird et al, 2009;Harrison, 2011).…”
Section: Marine Invertebrate Larvae Associated With Symbiodiniummentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of cnidarians, while broad knowledge on their association with Symbiodinium is available, there are still relatively few studies on the larva-Symbiodinium association (Rodriguez-Lanetty et al, 2006;Voolstra et al, 2009b;Schnitzler and Weis, 2010;Wolfowicz et al, 2016). Approximately 80-90% of reef-building coral species (Scleractinia) are broadcast spawners and acquire symbionts horizontally (Harrison and Wallace, 1990;Baird et al, 2009;Harrison, 2011).…”
Section: Marine Invertebrate Larvae Associated With Symbiodiniummentioning
confidence: 99%
“…Only recently, a study by Mohamed et al (2016) detected a transient period of differential expression involving a limited number of genes (3% of assayed transcriptome) 4 h after the exposure of Acropora digitifera planula larvae to a competent strain of Symbiodinium. While yet to be applied for larval studies, symbiosis-specific genes have been identified recently in Aiptasia anemones (Bucher et al, 2016;Wolfowicz et al, 2016). From the symbiont perspective, apart from the identification of protein kinases that may be involved in the establishment of symbiosis (Rosic et al, 2014), a symbiosisspecific gene was identified in Symbiodinium clade A, an H + -ATPase (Bertucci et al, 2010).…”
Section: Biochemical and Molecular Relationshipmentioning
confidence: 99%
“…Notably, studying the cnidarian–dinoflagellate symbiosis in corals is difficult for several reasons, including the challenges with maintaining corals in aquarium settings, long reproductive cycles and the obligate dependency on their symbiotic association, that is, the absence of a “control” aposymbiotic (symbiont‐free) state (Voolstra, ). To this end, the sea anemone Aiptasia (sensu Exaiptasia pallida ) is becoming increasingly popular as a model system for the study of coral–algal symbiosis (Baumgarten et al, ; Lehnert, Burriesci, & Pringle, ; Rädecker et al, ; Wolfowicz et al, ). Aiptasia is easily reared in laboratory tanks, has a short asexual reproductive cycle and can be kept in an aposymbiotic state, enabling direct comparison between symbiotic and aposymbiotic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We observed no evidence in our dataset indicating overall enrichment of SNPs strongly associated with PC1 in scavenger receptors ( p  =   .31; Neubauer et al., 2016) or genes differentially regulated during symbiosis establishment in larvae ( p =  .52; Wolfowicz et al., 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Larval settlement of Fungia scutaria , a scleractinian coral that also acquires symbionts horizontally, occurred earlier when larvae were colonized by Symbiodinium (Schwarz, Krupp, & Weis, 1999) . Exaiptasia larvae similarly take up Symbiodinium prior to settlement and metamorphosis (Wolfowicz et al., 2016). Additionally, both temperature and the identity of ex‐hospite symbiont types can influence settlement behavior and substrate choice in larvae of broadcast‐spawning corals (Winkler, Pandolfi, & Sampayo, 2015).…”
Section: Discussionmentioning
confidence: 99%